TOLOK UKUR PEMBINAAN TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN DALAM PERSPEKTIF TUJUAN PEMIDANAAN DAN HAK ASASI MANUSIA - Reynaldi Reynaldi; Evi Deliana; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The community system besides aiming to restore community-assisted citizens asgood citizens also aims to protect the community against the possibility of repeatingcriminal acts by correctional assisted residents, and is an application and an inseparablepart of the values contained in Pancasila. Realizing this, for a long time the Indonesiansocial system has been more emphasized on the aspects of coaching prisoners, communityprotégés or community clients who have preventive, curative, rehabilitative andeducational characteristics. In relation to punishment, that the purpose of punishment hastwo main aspects, namely, first, aspects of community protection against criminal acts,second, aspects of protection of individuals or perpetrators of criminal acts. In addition, itoften happens that prisoners who are not very familiar with the rough life that should beresocialized through coaching in prisons, but after undergoing a period of punishmentsufficient to be able to accept the prisonization process, apparently have behaviors thatlead to a hard and rough life that characterizes most of the prisoner subcultures. So weoften hear that prisons are schools for inmates who want to get to a higher level of crime.This type of research is normative research, which is research conducted withliterature studies in the search for data. This research is descriptive which provides datathat is as accurate and detailed as possible on existing problems. In this writing, it usesqualitative data analysis which means explaining and concluding about the data that hasbeen collected by the author. This study uses secondary data or scientific data that hasbeen codified.The results of this study explain that there are still many human rights violations inprisons, such as discrimination, torture, and even murder. This is a violation of humanrights that often occurs in prisons so that counseling, supervision, and fair lawenforcement are needed to prison officers who commit human rights violations. There arestill many prisons that do not apply aspects of the purpose of punishment itself, where thesuccess of the purpose of punishment itself is inseparable from the role of the prisonofficers themselves. Furthermore, the lack of community participation in order toparticipate in the development of prisoners. It is hoped that correctional officers can fixthe acts of violence committed by prison officers because these actions can tarnish thehuman rights values of prisoners and for the community so that they can slowly reduce thestigma and perspective on prisoners so that when they return to society inmates do not feelexcluded so as not to repeat the same mistakes in the future.Keywords: Convict Training-Prisoners–Purpose of Sentencing–Human Rights